Outpatient Antibiotic Dispensing for the Population with Government Health Insurance in Syria in 2018-2019 - Saleh Aljadeeah; Veronika J. Wirtz; Eckhard Nagel (MDPI AG, 2020)
Little is known about antibiotic uses at the population level in Syria. The aim of our study is to present outpatient antibiotic dispensing (OAD) patterns and rates for patients with health insurance in the parts of Syria that are controlled by the Syrian government using different indicators. Outpatient data on all dispensed antibiotics for 81,314 adults with health insurance were obtained and stratified according to age, sex, governorate and annual season. OAD was mainly expressed as the number of defined daily doses (DDDs) per 1000 people per day (DID). OAD patterns were assessed according to the anatomical therapeutic classification (ATC) and the Access, Watch and Reserve (AWaRe) classification. OAD was 20.13 DID. Amoxicillin/clavulanic acid and clarithromycin were the most dispensed antibiotics (5.76 and 4.4 DID, respectively). Overall, a predominant consumption of broad-spectrum antibiotics was noted. The Watch group of the AWaRe classification had the biggest percentage of OAD (13.26 DID), followed by the Access and the Reserve groups (6.55 and 0.17 DID, respectively). There was a significant difference in OAD between the sex and age groups. The seasonal and regional variations in OAD were also significant. Broad-spectrum antibiotics dispensing was high compared to other studies from different countries. These results are concerning, as they can contribute to antibiotic resistance.